Supporting Families in Reviewing and Communicating about Radiology Imaging Studies - Hong, Matthew K; Feustel, Clayton; Agnihotri, Meeshu; Silverman, Max; Simoneaux, Stephen F; Wilcox, Lauren (Proceedings of the SIGCHI conference on human factors in computing systems. CHI Conference, 2017)
Diagnostic radiology reports are increasingly being made available to patients and their family members. However, these reports are not typically comprehensible to lay recipients, impeding effective communication about report findings. In this paper, we present three studies informing the design of a prototype to foster patient-clinician communication about radiology report content. First, analysis of questions posted in online health forums helped us identify patients' information needs. Findings from an elicitation study with seven radiologists provided necessary domain knowledge to guide prototype design. Finally, a clinical field study with 14 pediatric patients, their parents and clinicians, revealed positive responses of each stakeholder when using the prototype to interact with and discuss the patient's current CT or MRI report and allowed us to distill three use cases: co-located communication, preparing for the consultation, and reviewing radiology data. We draw on our findings to discuss design considerations for supporting each of these use cases.